2020
DOI: 10.1371/journal.pone.0232363
|View full text |Cite
|
Sign up to set email alerts
|

A biological control model to manage the vector and the infection of Xylella fastidiosa on olive trees

Abstract: Xylella fastidiosa pauca ST53 is the bacterium responsible for the Olive Quick Decline Syndrome that has killed millions of olive trees in Southern Italy. A recent work demonstrates that a rational integration of vector and transmission control measures, into a strategy based on chemical and physical control means, can manage Xylella fastidiosa invasion and impact below an acceptable economic threshold. In the present study, we propose a biological alternative to the chemical control action, which involves the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…More recently, the occurrence of the egg parasitoid Ooctonus vulgatus Haliday was reported in Corsica [ 95 ]. The predation dynamics of the generalist predator Zelus renardii Kolenati on P. spumarius were reported by Liccardo et al [ 96 ]. Furthermore, Molinatto et al [ 97 ] reported the infestation of field-collected spittlebugs by the parasitoid fly Verrallia aucta Fallén.…”
Section: Current Attempts To Control the Insect Vector(s) In Olives—state Of The Artmentioning
confidence: 73%
“…More recently, the occurrence of the egg parasitoid Ooctonus vulgatus Haliday was reported in Corsica [ 95 ]. The predation dynamics of the generalist predator Zelus renardii Kolenati on P. spumarius were reported by Liccardo et al [ 96 ]. Furthermore, Molinatto et al [ 97 ] reported the infestation of field-collected spittlebugs by the parasitoid fly Verrallia aucta Fallén.…”
Section: Current Attempts To Control the Insect Vector(s) In Olives—state Of The Artmentioning
confidence: 73%
“…Following the discovery of X. fastidiosa in Europe, namely of the subsp. pauca transmitted to olive by P. spumarius, interest in biological control agents of this pest has greatly increased and has prompted research on natural enemies, namely an egg parasitoid, O. vulgatus [20] and a generalist predator, Z. renardii [21]. Verrallia aucta does not rapidly kill the host, which can survive until late in the season.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, very recently, one of the oophagous parasitoids recorded from US, Ooctonus vulgatus Haliday, has been found commonly and locally abundant in Corsica island of France [20]. Finally, the newly introduced predatory bug Zelus renardii Kolenati (Hemiptera, Reduviidae) has been proposed for the inundative control of P. spumarius with the aim of suppressing the spread of X. fastidiosa in olive groves of Apulia [21]. However, the mass release of such a generalist predator may be risky for local biodiversity, especially for beneficial arthropods [22], while its efficacy under field conditions has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Xf can be limited by agronomic practices affecting the vector Philaenus spumarius (Liccardo et al, 2020;Schneider et al, 2020) and, possibly, by acting on the soil microbiome (Fernández-González et al, 2019). However, replanting with resistant genotypes appears as the most feasible and promising strategy to control the bacterium.…”
Section: Introductionmentioning
confidence: 99%